The Impact of Coopetition on Business Value Creation : Amazon Experience - Baghirli, Aghakhan; Halík, Jaroslav, 1961-; Olšanová, Květa; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
This thesis addresses the single-case study on Amazon company experience, which can be presented as a successful example of coopetition business model adoption, while notwithstanding the arisen challenges. Knowledge leakage, tension, and opportunistic behavior are some of them triggered by the coopetition process. High-tech sector is an example where this context is mainly suitable, and yet meant to be as complex phenomena to manage. Thus, we would analyze how the value creation can be facilitated via adjusting coopetition to the company’s business strategy, and what are the main challenges in its execution.
Vedoucí práce: Jaroslav Halík
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses